2022
DOI: 10.3390/su14105777
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adoption Intention for Electric Vehicles under a Subsidy Deduction: From Different City-Level Perspectives

Abstract: The popularization of electric vehicles (EVs) is beneficial to the sustainable development of energy and the environment. China’s promotion and development strategy for EVs will serve as a model for other countries. EV ownership has a significant difference between first/second-tier (FST) cities and third/fourth-tier (TFT) cities and there is a huge growth potential for the EV market in those TFT cities. This paper aims to explore the factors influencing the adoption intentions for EVs in FST and TFT cities un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 101 publications
2
13
0
Order By: Relevance
“…For Hypothesis 4, the empirical results show that the positive effect of environmental consciousness on the purchase intention of GTTT products is significant (Table 7), and Hypothesis 4 is supported, which indicates that consumers with a stronger environmental consciousness are more likely to purchase GTTT products. Environmental consciousness is one of the important factors influencing consumers to purchase new green products [47][48][49], and Zhang et al [9] found that environmental consciousness significantly and positively influenced the purchase intention of electric vehicles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For Hypothesis 4, the empirical results show that the positive effect of environmental consciousness on the purchase intention of GTTT products is significant (Table 7), and Hypothesis 4 is supported, which indicates that consumers with a stronger environmental consciousness are more likely to purchase GTTT products. Environmental consciousness is one of the important factors influencing consumers to purchase new green products [47][48][49], and Zhang et al [9] found that environmental consciousness significantly and positively influenced the purchase intention of electric vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…Control variables: In accordance with related studies [66,67], we controlled for variables such as gender, age, level of education, household size, number of children, level of income, and occupation. In addition, the presence or absence of local licensing policies, the presence or absence of local subsidy policies [68], and the sizes of the individual influence of licensing subsidies can also impact the decision of consumers in China to purchase electric vehicles [9,69]; therefore, these variables were also included as control variables in this paper.…”
Section: Plants and Animals Have As Much Right To Live As Humans Domentioning
confidence: 99%
See 1 more Smart Citation
“…Attitude toward using ECs was measured using three items from [70]. Finally, ECs adoption intention was assessed using four items [71,72]. These measurement scales were selected based on their utility and relevance to ensure the comprehensiveness and accuracy of our research findings (Appendix A).…”
Section: Study Questionnairementioning
confidence: 99%
“…TAM's goal is to unravel the factors that influence consumers' adoption of new technologies. The study by [12] was conducted using a variety of methods to identify factors that facilitate or compel human adoption of SDs, and to identify consumer adoption [13], purchase [14], and usage [15] intentions. Consumers' intention to use electric and hybrid vehicles is related to how well factors such as technology perception, price, availability, and information are controlled.…”
Section: Introductionmentioning
confidence: 99%